Cheating behaviour among accounting students: Some Malaysian evidence - Ismail, Suhaiza; Yussof, Salwa Hana (Emerald Group Publishing Limited, 2016)
Purpose – This study aims to examine the cheating behaviour among accounting students in terms of the extent of neutralization of cheating and the effectiveness of deterrents to cheating of cheaters and non-cheaters. It also aims to examine the differences in the cheating behaviour between males and females of cheaters and non-cheaters groups.